Memahami Pengetahuan Guru tentang Pendidikan Jasmani yang Bermakna dalam Konteks Komunitas Praktik: Sebuah Studi Perbandingan Lintas Sektoral - Hilda Ilmawati; Tite Juliantine; Agus Mahendra; Sucipto Sucipto; Gita Febria Friskawati (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Teachers' understanding of Meaningful Physical Education (Meaningful PE) is a key aspect in promoting meaningful learning experiences for students. While various professional development programs, such as Communities of Practice (CoP), have been implemented, empirical evidence regarding teachers' understanding based on professional characteristics remains limited. This study aims to analyze physical education teachers' level of understanding of Meaningful PE and examine differences based on gender and years of teaching experience. Materials and methods. The study used a quantitative survey design with a cross-sectional approach towards 66 physical education teachers who regularly participated in CoP. The instrument used was a Likert scale questionnaire (1–5) consisting of 16 statements related to conceptual understanding of Meaningful PE, which had an r = 0.873. The data were analyzed using the One-Way ANOVA test and the Tukey test. Results. The findings indicate that gender is not a significant differentiating factor in teachers' knowledge levels, whilst teaching experience contributes significantly to variations in knowledge. These results confirm that professional experience and involvement in collaborative learning communities play a greater role in shaping teachers' pedagogical literacy than demographic characteristics. Conclusions. This study reinforces the urgency of community-based continuing professional development to improve teachers' conceptual understanding of meaningful physical education pedagogy.